TIME CALCULATION AND STANDARD OUTPUT ON HULLER MACHINE DESIGN OF DRY COFFEE SKIN SEPARATE MACHINE SEMI-AUTOMATIC ENTERPRISES ASHARI JAYA - Sari, Sheila Setya; Widhy Wahyani (Bajang Institute, 2024)
The stage of separating the coffee bean shell is one of the important processes in coffee processing. The separation of the coffee bean husks at the Ashari Jaya MSME uses two different machines so this separation process is carried out in two processes because during the process of separating the coffee bean husks in machine 1 it is still mixed with the peeled skin so it requires machine 2 to make these dry coffee beans clean from remaining skin mixture. The purpose of this machine design is to combine two machines into one, making it easier for workers to operate the machine, as well as more ergonomic in terms of size. With the dry coffee bean huller machine, it is hoped that it can increase the productivity of peeling dry coffee beans as well as relieve workers from the workload and reduce the risk of work accidents. The research method in designing this semi-automatic dry coffee bean huller machine includes conducting a survey of MSMEs processing Ashari Jaya coffee beans, identifying problems with these MSMEs, and formulating problems obtained from data collection. Furthermore, the data obtained were processed using the time and motion study method as a method of designing a machine operator work system accompanied by a data similarity test, and a data sufficiency test to determine the standard time and standard output. From the results of this study, it can be seen that testing using the old machine obtained a standard time of 2.8 minutes/kg and testing using a new machine obtained a standard time of 11.8 minutes/kg, then the increase in production productivity is 0.06 kg/second and the percentage increase in standard output by 88% with a productivity ratio of 1: 2.2